Basophils activation of patients with chronic spontaneous urticaria in response to C5a despite failure to respond to IgE-mediated stimuli - Matsubara, Daiki; Yanase, Yuhki; Ishii, Kaori; Takahagi, Shunsuke; Tanaka, Akio; Ozawa, Koichiro; Hide, Michihiro (Frontiers in Immunology, 2022)
Urticaria is characterized by the occurrence of wheals and flares in response to vasoactive mediators, such as histamine. Various studies have suggested the involvement of basophils in the pathogenesis of chronic spontaneous urticaria (CSU). However, histamine release from peripheral basophils in response to stimuli acting on the high affinity IgE receptor (FcεRI) is impaired in many patients with CSU (non/low responders). We previously demonstrated that tissue factor (TF)s expressed on vascular endothelial cells in response to a combination of various stimuli, such as that of histamine and lipopolysaccharide (LPS), activates the extrinsic coagulation pathway and produces anaphylatoxin, complement 5a (C5a), which then activates basophils and mast cells via the C5a receptor (C5aR). We have revealed that histamine release was induced in response to C5a and formyl-l-methionyl-l-leucyl-l-phenylalanine (fMLP), regardless of the response to anti-IgE antibody, the reduced numbers of basophils and severity of urticaria. Moreover, we found that spontaneous release of histamine ex vivo from basophils of patients with CSU is higher than that from healthy individuals. These results suggest that basophils and the complement system, which could be activated by coagulation factors, may play a critical role in the pathogenesis of CSU, especially in cases refractory to treatment involving the IgE/FcεRI pathway.